2021
DOI: 10.3390/healthcare9070860
|View full text |Cite
|
Sign up to set email alerts
|

Back Pain Prevalence, Intensity, and Associated Risk Factors among Female Teachers in Slovakia during the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Significant back pain prevalence and intensity are reported in female pedagogues. Due to the COVID-19 pandemic, they have been exposed to remote working conditions, higher psychological demands, and stress. Our objective was to evaluate the back pain prevalence, intensity, and related risk factors in female teachers from Slovak regions in the context of remote learning during the COVID-19 pandemic. An electronic questionnaire was applied for data collection. A total of 782 adult female teachers (age 43.11 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
3
20
1
3
Order By: Relevance
“…Consistent with other studies, we discovered that LPB is more common in people who rarely or never exercise 5,10,20,32,35) . LBP is caused by shortened and weakened back muscles, which causes spinal misalignment.…”
Section: Risk Factors Of Lbp In Middle Age Adultsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with other studies, we discovered that LPB is more common in people who rarely or never exercise 5,10,20,32,35) . LBP is caused by shortened and weakened back muscles, which causes spinal misalignment.…”
Section: Risk Factors Of Lbp In Middle Age Adultsupporting
confidence: 92%
“…In line with previous research, we discovered that the prevalence of LBP was higher in females than in males 7,19,27,35) . Females have a 8 lower pain threshold than men, so they are more likely to report LBP symptoms than men 28,32) . Other research has found that females are at a higher risk of LBP due to hormonal imbalances.…”
Section: Risk Factors Of Lbp In Middle Age Adultmentioning
confidence: 99%
“…In this sense, studies among teachers reveal that lower back pain is significantly associated to job provisions, work environment satisfaction ( 52 ) and the female gender ( 53 ). Additionally, a study during the health crisis by COVID-19 indicates that more than 60% of teachers have some back pain associated with non-performance of PA, non-compliance with ergonomic recommendations, and stress ( 54 ). In that vein, the highest pain associations have been reported with extremely severe depression, extremely severe anxiety and high psycho-social work demands among secondary teachers ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Doniesienia o bólu odcinka lędźwiowego kręgosłupa po przejściu na tryb pracy zdalnej sugerują, że społeczne i ekonomiczne obciążenie tymi schorzeniami zwiększy się po zakończeniu pandemii COVID-19 [18]. Podobne badanie dotyczące czynników ryzyka wystąpienia bólu kręgosłupa u nauczycieli przeprowadzono na Słowacji [19] i uzyskano zbliżone wyniki, świadczące o tym, że pandemia wywarła niekorzystny wpływ na tą grupę zawodową.…”
Section: Omówienieunclassified